The dynamics of Hong Kong's office rental market - Hui, Eddie Chi Man; Yu, Ka Hung (International Journal of Strategic Property Management, 2010)
Forecasting office rents is among the most researched topics in real estate study. However, there are still heated debates on how predictions can be best done. This study provides a generator approach, on the basis of both system dynamics and econometric modeling. The findings suggest that the office rental values in Hong Kong appear to be more volatile and uncertain under better economic conditions, likely due to both the supply side of the property market being over‐optimistic of economic trends and the development lags and adjustment cost, under the influence of the current land policies in Hong Kong, are the main issues behind this phenomenon. In order to minimize the uncertainties on the office leasing market, the government should relax the approval procedures concerning changing land use, and the subsequent rearrangements of premium payment. Further, the current policies on land sales need to be revised, especially the application list system. Those measures could reduce the time and transaction cost incurred, thus leading to more timely response to demand changes over time.First Published online: 18 Oct 2010